Transforming dementia research into practice: a multiple case study of academic research utilization strategies in Dutch Alzheimer Centres - Eden Meng Zhu; Martina Buljac-Samardžić; Kees Ahaus; Robbert Huijsman (Health Research Policy and Systems)
Abstract Background Non-pharmacological dementia research products, such as social and behavioural interventions, are generated in traditional university settings. These often experience challenges to impact practices that they were developed for. The Netherlands established five specialized academic health science centres, referred to as Alzheimer Centres, to structurally coordinate and facilitate the utilization of dementia research knowledge. This study leverages implementation science to systematically explore the research utilization strategies used by academic researchers from each Alzheimer Centre, on the basis of the “knowledge-to-action” (KTA) framework that includes knowledge creation, adaptation, dissemination and implementation. Methods Individual semi-structured qualitative interviews were conducted with 29 respondents across the five Alzheimer Centres in the Netherlands. Participants were selected through purposive (snowball) sampling. Interviews were conducted in-person and virtually through Microsoft Teams, and all were audio-recorded and transcribed verbatim. Data analysis was guided by the dimensions of the KTA framework. Result There was a high variation in the strategies used across the five Alzheimer Centres to bring non-pharmacological dementia research into practice. Selected strategies in each Centre were influenced by the typology of research products produced and the Centres’ organizational heritage. The knowledge creation and adaptation phases were mainly facilitated by funders’ guidance towards research impact and research product co-creation with patients and implementing organizations. Dissemination and implementation phases were often facilitated through utilizing support from university-based technology transfer offices to facilitate implementation and valorization and establishing and strategically leveraging formal infrastructure, such as public–private partnerships and professional collaborative networks. Conclusions Successful research utilization requires evolving researcher competencies to meet environmental demands and facilitating co-creation with research end-users and implementing partners. Understanding external determinants influencing research utilization in the Dutch dementia research ecosystem is crucial for capacity-building and aligning cross-sector agendas. The KTA framework appears to reveal the intricacies of research utilization, guiding future studies to explore strategies employed across various contexts.